2021
DOI: 10.5946/ce.2020.058
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Intravenous Fluorescein Dose for Upper and Lower Gastrointestinal Tract Probe-Based Confocal Laser Endomicroscopy

Abstract: The development of probe-based confocal laser endomicroscopy (pCLE) has allowed endoscopists to observe gastrointestinal (GI) lesions with thousand-fold magnification and real time in vivo histologic evaluation of the lesions. 1 Several prior studies have already shown the usefulness and safety of optical biopsy using pCLE in the field of gastroenterology 2-5 and it has further been reported that pCLE is relatively easy to learn. 6,7 Intravenous (IV) fluorescein is an essential contrast agent required to obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Moreover, the intravenous fluorescein administration (dose 4–8 mg/kg) can lead to adverse reactions, including nausea, vomiting, and rash at the injection site, in more than 1% of cases 98 . Recently, Inoki et al 99 . revealed that by reducing the dose of fluorescein to 0.5 mg/kg, tissue structure visualization of all colorectal neoplasias remained optimal (12/12 lesions, 100%), with no serious adverse reactions.…”
Section: Advanced Imaging Techniquesmentioning
confidence: 99%
“…Moreover, the intravenous fluorescein administration (dose 4–8 mg/kg) can lead to adverse reactions, including nausea, vomiting, and rash at the injection site, in more than 1% of cases 98 . Recently, Inoki et al 99 . revealed that by reducing the dose of fluorescein to 0.5 mg/kg, tissue structure visualization of all colorectal neoplasias remained optimal (12/12 lesions, 100%), with no serious adverse reactions.…”
Section: Advanced Imaging Techniquesmentioning
confidence: 99%